(untitled) (Conversatoria Linguistica, 2022)
In this article, I will deal with the issues of the in herited language and the language of ancestors in the Ukrainian-Romanian, Ukrainian-Moldavian and Ukrainian-Russian borderlands. The aim of this article is to show the sociopolitical influences on the transmission of the language in Polish families. Examples of the use, language transmission and learning of the Polish language in the aforementioned border lands will be shown as an example. The criteria for defining Polish as the ancestral language or the language inherited by the interlocutors emerged during the analysis of the linguistic biographies of my interlocutors. These theoretical considerations were based on practical material. The inheritance of the Polish language of two interlocutors was influenced, among others, by being born in a Polish family, close neighborhood, which also spoke Polish; maintaining Polish traditions; practicing religion. The lack of transmission of the Polish language among the interviewee, who was born in the Luhansk region, was due to the fact that her parents did not speak Polish, the father hid his Polish origin, fear of repression and de-portation, living in an urban environment, and lack of contacts with people of Polish origin. This interlocutor started to learn the Polish language as an adult as the language of her new identity, and what is very important, she instilled in children and grandchildren a sense of Polish identification.